Modelling of a vacuum metallization patterning method for organic electronics - Cosnahan, T; Watt, A; Assender, H (Elsevier, 2017)
The high throughput roll-to-roll patterning of metal thin films could be used to create organic functional devices. In this paper we present research into the compatibility of an in-vacuum selective metallization technique, which uses a sacrificial oil to define the metal electrode pattern for functional devices. The exact mechanism of the sacrificial oil masking, pattern definition and oil vaporization, due to the radiant heating from the thermal evaporation source, is described from previous research and experimental findings. The thermal modelling of this process develops further the requirements for the masking oil. It is found that in this particular system the oil thickness must be 1.63 ± 0.31 μm to match the radiative energy, and not be evaporated prior to leaving the metallization zone or to remain, as excess, after metallization is complete. The temperatures required are low and compatible with heat sensitive functional organic materials. The definition of the metal pattern edges is found to be like the liquid oil but thermal modelling still supports the theory of the oil vapor having the largest masking effect and concludes that the pattern definition quality does not depend on the sacrificial oil masking or vaporization effects but on the flexography patterning.